2003
DOI: 10.1248/cpb.51.1283
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Route to 3-Benzoheteroepines Containing Group 15 and 16 Heavier Elements Involving Several Novel Ring Systems, and Their Thermal Stabilities

Abstract: The C-unsubstituted 3-benzoheteroepines (2a-g) containing group 15 (P, As, Sb, and Bi) and group 16 (S, Se, and Te) heavier elements were prepared by the reaction of the corresponding metal reagents with (Z,Z)-obis(b b-lithiovinyl)benzene (5) which was derived in two steps from a common o-phthalaldehyde (3). The heteroepines (2) thus obtained were thermally labile towards heteroatom extrusion, and their half-lives on heating estimated from 1 H-NMR spectral analysis showed that the 3-benzoheteroepines (2) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Illustrative is the condensation of 5 with PhPH 2 -Mn(CO) 2 Cp that gives manganese-complexed phosphepine 7b (35%). The molecule in the crystal shows again C s -symmetry, but has a flatter phosphepine ring with a dihedral angle of 34.49 (8)°b etween the C1-P1-C1i and hydrocarbon planes (Figure 2). This is best explained by a steric effect of the Cp, hanging over the phosphepine ring, in which CdC bond alternation is again evident.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Illustrative is the condensation of 5 with PhPH 2 -Mn(CO) 2 Cp that gives manganese-complexed phosphepine 7b (35%). The molecule in the crystal shows again C s -symmetry, but has a flatter phosphepine ring with a dihedral angle of 34.49 (8)°b etween the C1-P1-C1i and hydrocarbon planes (Figure 2). This is best explained by a steric effect of the Cp, hanging over the phosphepine ring, in which CdC bond alternation is again evident.…”
mentioning
confidence: 99%
“…12 The more shielded 31 P NMR resonance at +64 ppm points to less electrophilic character for the phosphorus group than in 7a; the 1 H and 13 C NMR parameters are similar, including the 2 J HP (20.7 Hz) and 3 J HP (32.1 Hz) coupling constants. Phosphepines 8 and 9 are known to decompose readily to the aromatic hydrocarbon and (RP) 5 , presumably by expelling [RP] from the NCD intermediates 7,8 (Chart 1). Interestingly, in the case of complex 7 this would result in the expulsion of a transition metalstabilized phosphinidene [R-PdML n ].…”
mentioning
confidence: 99%
“…Notably, the mass spectrum of 2,7-di-tert-butylthiepine does not show ions generated by the loss of sulfur, an observation that is unexpected. [82] Tautomerism in azepines via an allowed 1,5-hydrogen shift has been studied for different azepine isomers and it was found that the ratio of azepine tautomers is related to their relative thermal stabilities [69d, 86]. For instance, when heated in toluene both 2H-and 3H-azepines 2 and 3 are converted into mixtures containing the 2H-, 3H-, and 4H-azepine tautomers in similar ratio (about 10: 50: 1).…”
Section: Extensivementioning
confidence: 99%
“…However, 3-benzothiepine (20) has been prepared from phthalaldehyde [224] under the conditions shown in Scheme 21.62.…”
Section: Synthesis Of Benzoxepinesmentioning
confidence: 99%
See 1 more Smart Citation